Performanceof lactating dairy cows fed yeast and fibrolytic enzymes - Titgemeyer, Evan C.; Johnson, B.J.; Shirley, John E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We evaluated the effect of supplementing typical dairy diets with yeast and fibrolytic enzymes on dairy cow performance. Twentyfour Holstein cows were used to evaluate the effects of yeast (Procreatin-7, a live culture of Saccharomyces cerevisiae) and various amounts of FP800 (a fibrolytic enzyme mixture) on lactation performance. Treatments were arranged in a 4 × 2 factorial design consisting of 8 treatments: 0, 5, 10, or 15 g of FP800 per day and 0 or 5 g of Procreatin-7 per day. Design and conduct of the experiment allowed at least 10 observations in each of the 8 treatment combinations. Within each 28- day period, the first 2 weeks were used for adaptation to treatment and the next 2 weeks were used for measuring feed intake and milk production. Diets were fed individually to each cow twice daily. The diet contained 22% ground corn, 20% corn silage, 20% wet corn gluten feed, 17% alfalfa, 8% whole cottonseed, and 8% expeller soybean meal. Dietary protein was 19% of dry matter. Treatments were top-dressed to the diets. Cows were milked twice daily. Dry matter intake averaged 64.6 lb/day, milk production averaged 96.8 lb/day, and efficiency of milk production averaged 1.50 lb milk/lb dry matter intake. Dry matter intake, milk production, milk efficiency, and production of all milk components were not changed by addition of either fibrolytic enzymes or yeast. Percentages of fat, protein, and solids-not-fat (SNF) in milk were also not affected by treatment. The results demonstrated no production responses to the addition of fibrolytic enzymes or yeast to the diets of lactating cows under our experimental conditions.
Keywords: Dairy; Yeast; Milk yield; Fibrolytic enzymes